Ecological Status of Shallow Water Coral Reefs and Fish Communities in Tidung Island, Indonesia - Lisa Ipambonj; Muhammad Ramlan; Muhammad Hendy Abdullah (Yayasan Siti Widhatul Faeha, 2025)
Coral reefs play an important role in supporting biota diversity and providing environmental services, but are increasingly threatened by anthropogenic pressures and environmental change.This study aims to assess the Ecological status of shallow water coral reefs and fish communities in Tidung Island, Indonesia. Point Intercept Transect (PIT) method was used to measure coral cover and the data were analyzed using Coral Reef Coverage. Meanwhile, data on fish communities living in coral reefs were obtained from the Underwater Fish Visual Census (UVC) method. The results showed that overall coral cover was in moderate condition. Furthermore, the reef fish community was dominated by the Pomacentridae family (9 species) and followed by Scaridae (4 species). In addition, this study found that the composition of algae, abiotic components, and sponges reached 67% of the total cover. These findings highlight the urgent need for targeted conservation actions and sustainable management to restore coral reef health and maintain biodiversity in the coastal ecosystems of Tidung Island.